Irreversible tunability of through-thickness electrical conductivity of polyaniline-based CFRP by de-doping. (10th November 2017) - Kumar, Vipin; Yokozeki, Tomohiro; Goto, Teruya; Takahashi, Tatsuhiro; Dhakate, Sanjay R.; Singh, Bhanu P.
Abstract: Carbon fiber reinforced plastics (CFRPs) are known for their tunable mechanical properties but not for having tunable electrical properties. In this work, a composite CFRP based on conductive polyaniline (CF/PANI) was prepared, which demonstrates electrical conductivity that is controllable post-fabrication. A thermosetting matrix of PANI doped with dodecylbenzenesulfonic acid (DBSA) and dispersed in cross-linking divinylbenzene (DVB) polymer was used to impregnate carbon-fiber fabric. The electrical and mechanical properties of the CF/PANI composite were measured. For the first time, it was shown that thermal de-doping in PANI can be used to control the electrical conductivity of a CFRP made with PANI-based thermosetting matrix. An average electrical conductivity of 1.35 S/cm in the through-thickness direction of the CF/PANI is reported, which can be irreversibly reduced to a desired value by thermal annealing. UV-Vis and FT-IR spectroscopy were used to evaluate the doping quantitatively. Images obtained from an optical microscope fitted with a heating plate system demonstrate the de-doping of PANI. The mechanical properties of the composites were measured after each thermal treatment cycle to determine any deterioration; the irreversible modification of the CF/PANI's electrical conductivity occurs without any degradation of the mechanical properties.